Analisis Efisiensi Teknis Produksi Rumput Laut (Eucheuma Cottonii) di Kabupaten Situbondo, Jawa Timur Menggunakan Data Envelopment Analysis (DEA) - Anam, M. Khairul; Setyana, Sukma Febri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study analyzes the technical, allocative, and cost efficiency of Eucheuma cottonii seaweed production in Situbondo Regency, East Java, a major Indonesian producer. A census was conducted on 60 farmers in Agel Village and Pathek Beach. Primary data included inputs (seeds, plot area, labor, fuel) and output (dried seaweed production), analyzed using Data Envelopment Analysis (DEA) with DEAP 2.1, applying Constant Return to Scale (CRS) and Variable Return to Scale (VRS) approaches.The production process involves site preparation to harvesting (40-45 days), yielding 800-1,500 kg of dried seaweed per cycle. Average technical efficiency was 0.713 (CRS) and 0.873 (VRS), indicating that most inefficiencies arise from sub-optimal operational scale. Average allocative efficiency of 0.835 suggests farmers haven't fully optimized input combinations based on market prices. Average cost efficiency was only 0.799, with only 11.67% of farmers being cost-efficient, highlighting significant opportunities for improving operational cost management.Recommendations include enhancing farmers' managerial and technical capacity through training on efficient input use and business scale adjustment. Local government is encouraged to provide intensive assistance for optimizing input allocation and production cost management. Future research should consider a metafrontier DEA approach for cross-group or regional efficiency comparisons, and include variables like education level and experience for a more comprehensive analysis.